Explosive Initiation of Various Forms of Ti/2B Reactive Materials. Issue 3 (11th March 2014) - Clemenson, Michael D.; Johnson, Stephanie; Krier, Herman; Glumac, Nick
Abstract The reactivity of titanium and boron mixtures under detonation initiation in air is examined experimentally in a constant volume blast chamber. Fine powder mixtures and mechanical alloys are pressed into compacts and are ignited using an HMX‐based explosive initiated with both single point and triple point detonator configurations. Transient pressure measurements, optical imaging, pyrometry, and spectroscopy are performed to analyse the reaction. All mixtures show no significant enhancement in the primary blast wave strength, indicating a relatively slow reaction. However, measurable increases in overpressure are generated due to Ti and/or B reaction. It is found that Ti/2B mechanical alloys significantly outperform blended powder mixtures in generating larger overpressures, yielding energy releases of 45 % and 20 %, respectively. Triple point initiation of the mechanical alloys further enhances the overpressure generation when compared to single point initiation of the alloys, increasing the energy yield. The overpressure of blended powders is also exceeded by a TiB2 compound, suggesting that the intermetallic reaction may be less critical than previously thought. Detonation merging at the plane of interaction between explosive and Ti/2B material is shown to significantly enhance conversion. Spectroscopic measurements show the appearance of BO2 emission relatively late after detonation in the most reactive Ti/2B reactive mechanical alloys, and it appears strongest in system that show greatest reactivity.